Algorithmic tools for optimizing the temperature regime of evaporator at absorption-refrigeration units of ammonia production - Babichenko, Anatoliy; Kravchenko, Yana; Babichenko, Juliya; Krasnikov, Igor; Lysachenko, Ihor; Velma, Vladimir (Eastern-European Journal of Enterprise Technologies, 2018)
We analyzed evaporators at absorption-refrigeration plants in a secondary condensation unit of ammonia production as control objects. Coordinates of the vectors of state, control and external perturbations were determined. The necessity of solving the problem on minimizing the cooling temperature of a circulating gas at evaporators in order to improve the energy efficiency of production was substantiated. Based on the analysis of industrial hardware-technological implementation of units for primary and secondary condensation, we elucidated features of operating conditions of evaporators, which predetermine the parametric uncertainty in the functioning of control objects. The main one among these uncertainties is associated with the control action related to the consumption of reflux. By using the method of mathematical modeling, based on the developed algorithm, we defined patterns of control action related to the consumption of reflux on the efficiency of heat exchange processes at evaporators in the absorption refrigeration units. We have established the extreme character of dependence of the heat flow (cooling capacity) and the temperature of cooling a circulating gas on the consumption of reflux. Maximum cooling capacity, and therefore the minimum temperature of cooling a circulating gas at a certain temperature head, are predetermined by the achievement of a critical regime of the bubbling boiling of a refrigerant. A further increase in the temperature head with an increase in the consumption of reflux contributes to the establishment of the transitional regime and reduces effectiveness of the heat exchange surface. We determined indicators of energy efficiency for ammonia production, namely, natural gas consumption under conditions of change in the control action related to the consumption of reflux and values of coordinates for the perturbation vector. The developed algorithmic tools make it possible to carry out the task on minimizing the cooling temperature of a circulating gas using a gradient-free technique of the step type applying the methods for a one-dimensional search for an extremum. It is shown that minimizing the cooling temperature of a circulating gas could reduce annual natural gas consumption by 500 thousand nm3 on average.